Between the lines: an interpretative phenomenological analysis exploring injury, mental health and support in professional and semi-professional football in the United Kingdom - Alicia Powell; Daniel Gaffiero (Cogent Psychology, 2025)
Injuries among footballers present significant physical and psychological challenges. However, limited research has explored how injury affects the overall wellbeing of players across different levels of the sport. This study investigated the lived experiences of six male semi-professional and professional footballers, defined by the highest level they have played at, who sustained injuries necessitating prolonged absence from play, using Interpretative Phenomenological Analysis (IPA). In-depth semi-structured interviews revealed two overarching themes: (i) mental health challenges in football, including stigma surrounding psychological vulnerability, the emotional impact of injury and fear of re-injury; and (ii) support and resources in lower league football, highlighting limited psychological support and concerns around career and financial stability. Findings demonstrate that injury disrupts not only physical functioning but also psychological wellbeing and athletic identity. The stigma associating emotional struggle with weakness intensifies distress and deters help-seeking, complicating emotional adjustment and adherence to rehabilitation. These insights highlight the need for integrated rehabilitation frameworks that address mental health stigma, provide accessible psychological resources, and support career transitions - particularly for semi-professional players. Such interventions are vital for promoting players’ wellbeing and sustaining long-term football careers.